Skrining Fitokimia Ekstrak Daun Sungkai (Peronema canescens Jack.) Secara Infundasi Dan Maserasi - Ita Emilia; Andi Arif Setiawan; Dewi Novianti; Dian Mutiara; Rangga Rangga (Universitas PGRI Palembang, 2023)
The Sungkai plant has become a trending topic lately because of its benefits, which are believed by some people to be used in preventing the transmission of the COVID-19 virus by boiling some of its leaves using water. The purpose of this research was to examine the active ingredients contained in sungkai leaves (Peronema canescens Jacks) which were extracted by infundation (water solvent) and extracted by maceration (methanol solvent). The method used in this study is a qualitative chemical analysis. Phytochemical screening in this study, namely the alkaloid test (using Mayer, Wagner, and Dragendroff reagents), flavonoid test, tannin test, saponin test, steroid test, terpenoid test. Based on the results of the study, the results of the phytochemical screening of the methanol extract of sungkai leaves by maceration showed that all of the active compounds contained were positive, while the positive infundament extract contained flavonoids, steroids, terpenoids, tannins, saponins, but negative alkaloids.